Pengaruh Model Problem Based Learning Terhadap Kemampuan Koneksi Matematis Siswa di SMAN 2 Tambang Pekanbaru - Anggraini, Yola Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the effect of the Problem Based Learning model on students' mathematical connection abilities. The form of this research is a quasi-experiment (Quasi Experiment) and the research design is Nonequivalent Control Group Design with the sampling technique used, namely purposive sampling. This research was conducted from April 25 to May 28, 2024. The population of this study was all class X. The research sample was taken from two classes, namely the experimental class using the Problem Based Learning model and the control class using conventional learning. The data collection instruments in this study were implementation sheets, pretest and posttest sheets. The data collection technique was carried out using the test technique. The data analysis technique used was descriptive analysis and inferential analysis. Based on the descriptive analysis, it can be seen that the average mathematical connection ability of students has increased, where the experimental class has a higher average mathematical connection ability than the control class. Based on the Mann-Whitney U Test for non-normally distributed data, this study obtained the results that there is an effect of the Problem Based Learning model on students' mathematical connection abilities. So that the learning process carried out using the Problem Based Learning model in the study has improved.